Management of Sri Gethuk Waterfall Attractions - Anthon, Tino Asprilla; Triputro, R Widodo; Suharyanto, Suharyanto (International Journal Labs, 2021)
The management of Sri Gethuk Waterfall which is managed by the Tourism Village Business Unit under the Village-Owned Enterprise